2006
DOI: 10.1080/16501970500441807
|View full text |Cite
|
Sign up to set email alerts
|

LONG-TERM EFFECT OF LOW-FREQUENCY REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION OVER THE UNAFFECTED POSTERIOR PARIETAL CORTEX IN PATIENTS WITH UNILATERAL SPATIAL NEGLECT*Presented part by the 42nd Annual Congress of the Japanese Association of Rehabilitation Medicine in 2005.

Abstract: In this small pilot study, low-frequency rTMS over the unaffected posterior parietal cortex decreased unilateral spatial neglect for at least 6 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 9 publications
4
61
1
3
Order By: Relevance
“…Several studies have used this approach, and it has been shown to be effective in both motor and non-motor deficits. For example, inhibitory rTMS to the non-lesioned parietal cortex can induce long-lasting improvements in symptoms of spatial neglect (Brighina et al 2003;Shindo et al 2006). In the motor region, Grefkes and colleagues showed that inhibitory rTMS applied over contralesional M1 of patients with subacute stroke significantly improved motor performance of the affected hand (Grefkes et al, 2010).…”
Section: Strokementioning
confidence: 99%
“…Several studies have used this approach, and it has been shown to be effective in both motor and non-motor deficits. For example, inhibitory rTMS to the non-lesioned parietal cortex can induce long-lasting improvements in symptoms of spatial neglect (Brighina et al 2003;Shindo et al 2006). In the motor region, Grefkes and colleagues showed that inhibitory rTMS applied over contralesional M1 of patients with subacute stroke significantly improved motor performance of the affected hand (Grefkes et al, 2010).…”
Section: Strokementioning
confidence: 99%
“…Other studies with small right brain lesioned patient groups and no control condition, using low-frequency rTMS inhibiting the left parietal cortex are those of Shindo et al (2006), Koch et al (2008), Song et al (2009), andLim et al (2010). In the Shindo et al (2006) study, six sessions of rTMS improved the performance of two right brain-damaged patients on several subtests of the Behavioral Inattention Test (BIT) up to 6 weeks after treatment.…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%
“…In the Shindo et al (2006) study, six sessions of rTMS improved the performance of two right brain-damaged patients on several subtests of the Behavioral Inattention Test (BIT) up to 6 weeks after treatment. After a single low-frequency rTMS session, Koch et al (2008) observed an improvement in the naming of visual chimeric figures in 12 right brain-damaged patients and in the Song et al (2009) trial, two sessions of rTMS per day during 14 days ameliorated line bisection and line cancelation for up to 14 days after treatment in 7 patients with right brain damage.…”
Section: Non-invasive Brain Stimulationmentioning
confidence: 99%
“…Among patients with unilateral stroke, TMS of the unaffected parietal cortex reduced symptoms of contralesional visuospatial neglect. 71,81,131 In a pilot study of 2 patients with right hemispheric infarction who had unilateral spatial neglect, 2 weeks of TMS to the unaffected parietal cortex led to significant improvements in skills relevant to visual neglect. 131 In addition, TMS may also be effective in improving recovery from poststroke aphasias.…”
Section: Noninvasive Stimulation For Posttraumatic Cognitive Sequelaementioning
confidence: 99%
“…71,81,131 In a pilot study of 2 patients with right hemispheric infarction who had unilateral spatial neglect, 2 weeks of TMS to the unaffected parietal cortex led to significant improvements in skills relevant to visual neglect. 131 In addition, TMS may also be effective in improving recovery from poststroke aphasias. Aphasic patients show increased metabolic activation of the nondominant inferior frontal and superior temporal areas as evaluated by PET.…”
Section: Noninvasive Stimulation For Posttraumatic Cognitive Sequelaementioning
confidence: 99%